Decreased H3K9ac level of KLF4 mediates podocyte developmental toxicity induced by prenatal caffeine exposure in male offspring rats. (10th October 2019) - Zhu, Yanan; Chen, Haiyun; Zhao, Xiaoqi; Li, Bin; He, Hangyuan; Cheng, Hui; Wang, Hui; Ao, Ying
Highlights: PCE induces podocyte developmental toxicity in male offspring. Low expressional programming of renal KLF4 is involved in the toxicity by PCE. Glucocorticoid reduces the H3K9ac level of KLF4 and inhibites its expression. High level of glucocorticoid induced by PCE increases HDAC7 expression via GR. Abstract: This study aimed to verify the toxic effects of prenatal caffeine exposure (PCE) on the podocyte development in male offspring, and to explore the underlying intrauterine programming mechanisms. The pregnant rats were administered with caffeine (30 to 120 mg/kg⋅d) during gestational day (GD) 9 to 20. The male fetus on GD20 and the offspring at postnatal week (PW) 6 and PW28 were sacrificed. The results indicated that PCE caused ultrastructural abnormalities on podocyte, and inhibited the expression of podocyte marker genes such as Nephrin, Wilms tumor 1 (WT1), the histone 3 lysine 9 acetylation (H3K9ac) level in the Kruppel-like factor 4 (KLF4) promoter and its expression in the male offspring from GD20 to PW28. Meanwhile, the expression of glucocorticoid receptor (GR) and histone deacetylase 7 (HDAC7) in the fetus were increased by PCE. In vitro, corticosterone increased GR and HDAC7 whereas reduced the H3K9ac level of KLF4 and KLF4/Nephrin expression. KLF4 over-expression reversed the reduction of Nephrin expression, knockdown of HDAC7 and GR antagonist RU486 partially reversed the inhibitory effects of corticosterone on H3K9ac level and KLF4 expression. In conclusion, PCE caused podocyte developmental toxicity in male offspring, which was associated with corticosterone-induced low-functional programming of KLF4 through GR/HDAC7/H3K9ac pathway.